Tingkat Pengetahuan Stunting pada Ibu Hamil, Remaja Putri dan Ibu Yang Memiliki Anak Usia Dini di Kecamatan Badiri Wilayah Kerja Puskesmas Hutabalang Kabupaten Tapanuli Tengah Tahun 2023 - Ramlan Nasution; Esrina Sinaga; Ganti Tua Siregar (Jurnal Anestesi, 2024)
In the Indonesian context, efforts to prevent stunting have become the focus of government programs, such as the Supplemental Food Program and the Maternal and Child Health Program. However, the level of stunting is still quite high and shows that there is a gap in understanding and knowledge about stunting among pregnant women and mothers with young children. Stunting in pregnant women and mothers with young children and teenage girls is a serious public health problem. Factors that contribute to stunting include maternal nutritional status, access to health services, knowledge about nutrition, and environmental sanitation. This research aims to investigate knowledge about stunting in pregnant women, adolescent girls and mothers of early childhood in Central Tapanuli in 2023 It is hoped that the results of this research will provide important insights for developing more effective stunting prevention programs. There are several factors that influence knowledge, such as educational factors, information source factors such as social media, environmental factors, experience factors and age factors.